P163 Accuracy Of Inflammatory Markers To Distinguish Between Pneumonia And Pulmonary Embolism In Acute Settings. (10th November 2014) - Chishimba, L; Iqbal, F; Kasule, A; Joynson, A; Williams, J; Argawal, S; Hussain, I
Abstract : Backgroud: In emergency settings, the presence of significant rise in inflammatory markers in patients with acute respiratory symptoms suggest an alternative diagnosis rather than pulmonary embolism (PE), hence reduces the clinical probability of PE and the need for CTPA/VQ. However, it is increasingly recognised that PE is associated with abnormal concentrations of many proteins involved in inflammation and vascular injury, yet there is inadequate data describing the difference in these proteins from infective processes. Aims: We aimed to determine whether there is a difference in inflammatory markers between acute PE and community acquired pneumonia (CAP) or acute lower respiratory infection (LRTI). Methods: A random sample of emergency departments (ED) and patients evaluated for acute PE at our institution (January 2013–December 2013) were retrospectively evaluated for D-dimer, C-reactive protein (CRP) and serum white cell (WCC) levels. PE was diagnosed by a positive CTPA in all cases. Inflammatory markers in confirmed PE cases were compared and matched with those of community acquired pneumonia (CAP) and acute lower respiratory infection (LRTI). We excluded all cases with incidental, chronic or previous PE. Results: A total of 295 patients were included (mean age 67.7 ± 18.45 yrs; 159 males), of which 167 (56.6%) had PE, 58 (19.7%) had CAP, 63 (21.4%) LRTI and seven (2.4%) had other respiratory conditions (Table 1 ). The mean WCC (g/l) was similar between PE (10.9 ± 4.8), pneumonia (11.9 ± 5.2) and acute LRTI (12.2 ± 5.9) (p = 0.2). Similarly, there were no significant differences among disease groups for median CRP levels (mg/l); PE (67.3 (4–412); CAP (88.9 (12–417) and acute LRTI (median 68.9 (9–284), (p = 0.322). In contrast, levels of D-dimer were significantly higher in PE than CAP or ARTI) (p = 0.000). Conclusions: In patients suspected of acute PE, unlike D-dimer, levels of WCC or CRP do not reliably distinguish between PE, pneumonia or acute LRTI. These may not be relied upon to determine the clinical probability of PE.